Plant Growth Promoting Rhizobacteria, Arbuscular Mycorrhizal Fungi and Their Synergistic Interactions to Counteract the Negative Effects of Saline Soil on Agriculture: Key Macromolecules and Mechanisms - Alka Sagar; Parikshita Rathore; Pramod W. Ramteke; Wusirika Ramakrishna; Munagala S. Reddy; Lorenzo Pecoraro (Microorganisms, 2021)
Soil saltiness is a noteworthy issue as it results in loss of profitability and development of agrarian harvests and decline in soil health. Microorganisms associated with plants contribute to their growth promotion and salinity tolerance by employing a multitude of macromolecules and pathways. Plant growth promoting rhizobacteria (PGPR) have an immediate impact on improving profitability based on higher crop yield. Some PGPR produce 1-aminocyclopropane-1-carboxylic (ACC) deaminase (EC 4.1.99.4), which controls ethylene production by diverting ACC into α-ketobutyrate and ammonia. ACC deaminase enhances germination rate and growth parameters of root and shoot in different harvests with and without salt stress. Arbuscular mycorrhizal fungi (AMF) show a symbiotic relationship with plants, which helps in efficient uptake of mineral nutrients and water by the plants and also provide protection to the plants against pathogens and various abiotic stresses. The dual inoculation of PGPR and AMF enhances nutrient uptake and productivity of several crops compared to a single inoculation in both normal and stressed environments. Positively interacting PGPR + AMF combination is an efficient and cost-effective recipe for improving plant tolerance against salinity stress, which can be an extremely useful approach for sustainable agriculture.